Influencia de la edad de corte y aditivos sobre la calidad nutricional del ensilaje de pasto Cuba-22 (Pennisetum purpureum x P. glaucum) - Dueñas Sabando, Lariza Anabella (2021)
This research was developed in the Teaching, Research and Liaison Unit, pasture and forage area, at Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López”, with the aim of evaluating the influence of cutting age and additives on the nutritional quality of Cuba-22 grass silage; it lasted twelve months, from August 2019 to July 2020. The factors under study were cutting age (45, 60, 75 and 90 days) and additives (molasses, urea and flour). The experimental unit was made up of a 10 kg capacity polyethylene bag. The nutritional quality variable was evaluated with percentages of dry matter, crude protein, fiber and ash. It is concluded that the cutting ages of the grass have a determining effect on the nutritional quality of the Cuba-22 grass silage, independent of the additives tested; the use of additives improves the content of dry matter, protein and ash, while the opposite effect occurs for the fiber content; and the interaction of the cutting age of the grass with the additives does not produce significant effects on the nutritional quality of the Cuba-22 grass silage.